PENETAPAN BENTUK FONOLOGIS DARI BUNYI YANG BERALTERNASI: SATU ASPEK TERPENTING DALAM SISTEM TATA BAHASA - I Wayan Pastika (Linguistik Indonesia, 2015)
The choice of a phonological representation can be overt or nonovert depending on its phonological environments in a morpheme. The right decision with respect to the phonological rule should define a right grammatical system on morphophonology. The phonological process according to Generative theory and its daughter, Optimality theory, considers the ‘input’ choice should be the most acceptable candidate among its alternative counterparts. The choice of the input is not just seen from one single phonological process of the morpheme in question, but it should be overtly identified from other processes. The derivation from the ‘input’ to the output does not always exhibit identically phonological representation of segmental sequences in a stem because distinctive features always interact to each other in accordance with the phonological environment. When each phonological segment keeps its features faithfully, then there is no phonological change happening from the input to the output. Therefore, the input or the underlying form of a morpheme in question is not always overtly recognised from the ouput, but it may occur beyond the phonetic representation.